European Standard for the Protection of Patients’ Lives - Kwiatkowski, Paweł (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2022)
The aim of the study it to reconstruct the European standard for the protection of patients’ lives in its substantive and procedural aspects. In the case-law of the bodies of the system of the Convention for the Protection of Human Rights and Fundamental Freedoms, the scope of the state authorities’ substantive and procedural obligation to protect the right to life in the health care system was defined for the first time by the European Commission of Human Rights in the decision of 22 May 1995 in Mehmet Işıltan v. Turkey, and then repeated in the case-law of the reformed Court in the decision on the admissibility in Powell v. United Kingdom. The study of the European standard for the protection of patients’ lives traces its history, from Mehmet Işıltan v. Turkey and Powell v. United Kingdom; through developments of the meaning of its substantive limb, as illustrated by Mehmet and Bekir Senturk v. Turkey, Asiye Genc v. Turkey, Aydogdu v. Turkey, and Elena Cojocaru v. Romania; to developments of the meaning of its procedural limb, as exemplified by Calvelli and Ciglio v. Italy, Wojciech Byrzykowski v. Poland, Šilih v. Slovenia, and Gray v. Germany; and finally covers the Court’s attempt to sum up its previous approach to the European standard for the protection of patients’ lives, as expressed in the case of Lopes de Sousa Fernandes v. Portugal.